The "Market Model" In Investment Management: Discussion - Mckibben, Walt (Journal of Finance, 1980)
Walt Mckibben, The "Market Model" In Investment Management: Discussion, The Journal of Finance, Vol. 35, No. 2, Papers and Proceedings Thirty-Eighth Annual Meeting American Finance Association, Atlanta, Georgia, December 28-30, 1979 (May, 1980), pp. 607-609